BUILDING INSTITUTIONAL READINESS: HOW EDUCATION, TRAINING, AND WORK DISCIPLINE SHAPE PERSONNEL PERFORMANCE IN A POLICE LOGISTICS BUREAU - Yandra Rivaldo (Postgraduate Management Journal, 2023)
This study examines the effect of education, training, and work discipline on personnel performance at the Logistics Bureau of the Regional Police of the Riau Islands (Biro Logistik Polda Kepri). Personnel performance in a public-sector logistics function is central to institutional readiness, yet it is shaped by human-resource conditions that have received limited empirical attention in this context. A quantitative associative design was used, with a census of all 43 personnel as respondents. Data were collected through a structured Likert-scale questionnaire and analyzed using multiple linear regression in SPSS 23, following classical assumption tests. The results show that education (t = 7.340; p = .000), training (t = 2.328; p = .025), and work discipline (t = 4.464; p = .000) each have a positive and significant partial effect on personnel performance, and the three variables jointly explain 95.0 percent of the variance in personnel performance (R² = .950; F = 246.779; p = .000). Education emerged as the most dominant predictor (β = .525), followed by work discipline (β = .321) and training (β = .184). The findings indicate that continuing-education pathways, mandatory training compliance, and consistent disciplinary enforcement are complementary levers for strengthening personnel performance in police logistics units, and the study offers practical implications for human-resource policy in similar public-sector settings.